2012
DOI: 10.1097/npt.0b013e31827374c1
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Intersegmental Trunk Coordination During Walking Are Related to Clinical Balance and Gait Function in Chronic Stroke

Abstract: Changes in segmental transverse ROM and coordination were associated with poor gait and with balance abilities in individuals with stroke. Interventions focusing on recovery of these movement characteristics may lead to better clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 38 publications
0
51
0
1
Order By: Relevance
“…Thus, it appears that differences in results may stem from differences in intervention methods involving the use of sling equipment. The balance ability of stroke patients is related to trunk intersegmental movement27 ) ; therefore, significant differences in improvement between groups after intervention must be due to the use of intersegmental exercise. Correspondingly, when no intersegmental exercise is used, no significant difference in improvement is observed between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that differences in results may stem from differences in intervention methods involving the use of sling equipment. The balance ability of stroke patients is related to trunk intersegmental movement27 ) ; therefore, significant differences in improvement between groups after intervention must be due to the use of intersegmental exercise. Correspondingly, when no intersegmental exercise is used, no significant difference in improvement is observed between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The lower walking speed might cause compensation of thoracic motion to pelvic movement. In literature, it was showed that persons after stroke used more thoracic ROM than pelvic transverse ROM in comfortable and equivalent walking speed (0.97 m/s-0.98 m/s) compared to subjects without disability [38]. This may be the reason why we could not find any statistically significant differences in the peak angle of horizontal pelvic motion.…”
Section: S361mentioning
confidence: 64%
“…Further studies combined with electrophysiology information (i.e. EMG) and muscles strength are necessary to help better understanding the mechanism about the control of pelvis with VR + BWSTT [38,39]. In addition, a larger sample size of random control trial study or multi-center design which compares VR + BWSTT, BWSTT only and over-ground training is warrant to draw further conclusion about the outcome of VR + BWSTT for gait disorder with persons after stroke.…”
Section: S361mentioning
confidence: 99%
“…AsM5 is located within the anterior parts of the MCA territory which is hypothesized to represent sensory and motor areas of the cortex, the right M5 location could be hypothesized to have a greater role in the regulation of trunk control than left.Early information about lesion location together with assessment of trunk control may help guide therapists in their treatment choices and emphasis in intervention, which ultimately may positively affect the patients overall function and independence. Several authors recommend interventions aimed at improving trunk control post stroke [13,14,[47][48][49][50][51], and this is also recommended in a recent systematic review [52].…”
Section: Clinical Relevancementioning
confidence: 99%